Clinical characteristics, morbidity and mortality following an emergency abdominal surgery in patients with COVID-19 - Pinares Carrillo, Daniel (2021)
Objective: To present the clinical characteristics, laboratory analyses, diagnosis, treatment and evolution of patients with SARS-CoV-2 infection who underwent an emergency surgery. Materials and methods: A multicenter, descriptive and retrospective study conducted in 45 patients who underwent an emergency surgery for acute (surgical) abdomen with a diagnosis of COVID-19 between April and August 2020. Results: Forty-five (45) patients with acute abdomen underwent surgery, out of which 55.55 % were men and 44.44 % were women, with a mean age of 48.33 years. The most frequently used diagnostic test for COVID-19 was the serology test (88.88 %). All the patients underwent a chest computed tomography scan which showed no alterations (31.11 %) and bilateral consolidation of the lungs (48.88 %). The most frequent diagnoses were acute appendicitis (64.44 %) and intestinal obstruction (15.55 %). Postoperative complications occurred in 16 patients (35.55 %). The most frequent complications were respiratory failure (15.55 %) and acute renal failure (13.33 %). Two patients (4.4 %) died due to severe respiratory failure. Conclusions: COVID-19 was diagnosed based on serology tests and chest computed tomography scan findings. The most frequent surgery was appendectomy. Low morbidity and mortality rates were observed in relation to those reported in the medical literature.